An Evaluation of Universal Screening for MRSA at the Ottawa Hospital - Longpre, Tara (Université d'Ottawa / University of Ottawa, 2012)
Statement of the problem: Methicillin-resistant Staphyloccocus aureus (MRSA) is a pathogen of increasing concern and is associated with higher hospital readmission rates, poorer prognosis, and increased mortality resulting in increasing costs to the Canadian healthcare system.1-13 Institutions have been challenged with developing effective infection control programs to prevent the spread of MRSA. The purpose of this thesis was to examine the clinical and cost-effectiveness of a universal MRSA screening intervention within a large tertiary care facility. Methods of investigation: The retrospective population-based observational study consisted of two periods. In the first period (24 months), patients admitted to the Ottawa Hospital underwent risk factor-based screening. In the second period (20 months), universal MRSA screening was implemented in which all patients were screened for MRSA upon admission. Results: The regression analysis demonstrated that the universal MRSA screening intervention was not effective in reducing the number of nosocomial MRSA cases. The economic analysis estimated that the universal MRSA screening intervention incurred an additional cost of $1.16 million/year with an estimated additional cost per patient screened of $17.76. Conclusions: The universal MRSA screening intervention was not clinically or economically effective. Further research is required to verify/dispute these findings in other settings.
Keywords: MRSA; Methicillin-resistant Staphyloccocus aureus; Universal screening; Screening